The Construction of Conforming-to-shape Truss Lattice Structures via 3D Sphere Packing. (March 2021) - van Sosin, Boris; Rodin, Daniil; Sliusarenko, Hanna; Bartoň, Michael; Elber, Gershon
Abstract: Truss lattices are common in a wide variety of engineering applications, due to their high ratio of strength versus relative density. They are used both as the interior support for other structures, and as structures on their own. Using 3D sphere packing, we propose a set of methods for generating truss lattices that fill the interior of B-rep models, polygonal or (trimmed) NURBS based, of arbitrary shape. Once the packing of the spheres has been established, beams between the centers of adjacent spheres are constructed, as spline based B-rep geometry. We also demonstrate additional capabilities of our methods, including connecting the truss lattice to (a shell of) the B-rep model, as well as constructing a tensor-product trivariate volumetric representation of the truss lattice — an important step towards direct compatibility for analysis. Highlights: An algorithm for constructing a truss lattice that fills the interior of a complex-shaped model, based on sphere packing. The truss lattice conforms to the shape of the model, independently of its orientation. Variants of the algorithm connect the truss lattice to a shell of the model, or construct a volumetric representation of the truss lattice. Applicable for generating microstructures and support structures for geometric models.